The new spymasters inside the modern world of espionage from the Cold War to global terror - Grey, Stephen (New York St. Martin's Press, 2015)
The old world of spying-dead-letter boxes, microfilm cameras, an enemy reporting to the Moscow Center, and a hint of sexual blackmail-is history. The spymaster's technique has changed and the enemy has, too. He or she now frequently comes from a culture far removed from Western understanding and is part of a less well-organized group. The new enemy is constantly evolving and prepared to kill the innocent. In the face of this new threat, the spymasters of the world shunned human intelligence as the primary way to glean clandestine information and replaced it with an obsession that focuses on the technical methods of spying ranging from the use of high-definition satellite photography to the global interception of communications. However, this obsession with technology has failed, most spectacularly, with the devastation of the 9/11 attacks. In this searing modern history of espionage, Stephen Grey takes us from the CIA's Cold War legends, to the agents who betrayed the IRA, through to the spooks inside Al-Qaeda and ISIS. Techniques and technologies have evolved, but the old motivations for betrayal-patriotism, greed, revenge, compromise-endure. Based on years of research and interviews with hundreds of secret sources, Stephen Grey's The New Spymasters is an up-to-date expos ťhat shows how spycraft's human factor is once again being used to combat the world's deadliest enemies.
Includes bibliographical references (pages 324-329) and index.
Keywords: Intelligence service--History--20th century